Comparison of Biochemical Effects Induced by Changle between Male and Female Rats Using NMR and ICP-MS Techniques - 吴惠丰 李晓晶 冯江华 李伟生 李中峰 廖沛球 吴亦洁 裴奉奎 (Journal of rare earths, 2006)
Metabolic profiles caused by rare earth complex were investigated using NMR and ICP-MS techniques. Male and female Wistar rats were treated orally with Changle （A kind of rare earth complex applied in agriculture to raise the production of crops） at dose of 2, 5 and 20 mg·kg^-1 body weight/day respectively for 90 d. Urine and serum samples are collected on 90 d. The relative concentrations of important endogenous metabolites in urine and serum are determined from ^1H NMR spectra and the contents of the four rare earth elements （La, Ce, Pr and Nd） constituting Changle in the serum samples are measured by ICP-MS technique. Changle-induced renal and liver damage in rats is found based on the increase in the amounts of the amino acids, trimethylamine N-oxide, N, N-dimethyglycine, dimethylamine, succinate, α- ketoglutarate and ethanol as well as rare earth concentrations. The similarities and differentiations are found in the alteration patterns of metabolites and rare earth concentrations in serum.